ANALISIS PENENTUAN HARGA POKOK PRODUKSI BERDASARKAN SISTEM ACTIVITY BASED COSTING - Ika Neni Kristanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
Calculation of the cost of production is precise and accurate is the thing to do by any company, because the calculation of the cost of production is right, will lead to the determination of the selling price of a product can be determined appropriately so that the company can know clearly the profit generated. Inaccuracy charging will cause distortion of the cost, which would result in distortion of the cost of mistakes costing, decision making, planning and control. This study has the objective to identify and analyze the calculation of the cost of production based on the traditional system and the system of Activity Based Costing (ABC) in the bakery Rotindo, and compared to determine differences in the magnitude of the cost of production in the bakery Rotindo. This type of research is quantitative descriptive for the implementation includes data, analysis and interpretation of the meaning of the data obtained. The results showed Activity Based Costing system provides that the cost of production is greater for kotak special and bal coklat, while for the bread of aneka rasa, krim mesis, coffee mocca, bon-bon, regge and tawar provide that cost of production are smaller than traditional systems. Differences that occur due to the imposition of overhead costs on any type of bread. On traditional systems overhead costs for each type of bread is only charged on a cost driver that is only the number of units produced, while the system of Activity Based Costing overhead costs charged to some cost driver, so that the system of Activity Based Costing is able to allocate activity costs to each type of bread appropriately based on the consumption of each activity. Keywords: Cost of production, traditional system, Activity Based Costing system (ABC).